The Effect of Cell Phone Use on Hearing Function among Young People 20-40 Years (Latakia University Journal -Medical Sciences Series, 2021)
Background and Objective: The aim of the study is to know the effects of using cell phones on the ear, especially hearing loss and other ear symptoms such as tinnitus, dizziness, and ear pain: The study sample included 107 patients, whose ages ranged from 20-40 years, and the study period lasted for a year from June 2019 to June 2020. The study included patients in ENT clinic. In Tishreen University Hospital, with a one-sided ear complaint (hearing loss - tinnitus - ear pain) or dizziness, clinical examination was conducted to rule out the other causes, and then an audiogram was conducted to study their auditory function.Methods: A case-control study. The sample was divided into two groups (cases and controls), considering the ear exposed to the mobile phone (Dominant ear) in the group of cases, while the opposite ear (Non-Dominant ear) of the same person was considered within the group of controls.Results: 42 cases of sensorineural hearing loss were seen in the dominant ear 39%, while only two cases were seen for sensorineural hearing loss in the non-dominant ear 1.8%.A direct correlation was observed between the pattern of sensorineural hearing loss at 4000-8000 Hz frequencies and cell phone use, which is proportional to the length of daily use of the cell phone and increases with the number of minute’s increase of daily use of the cell phone.A prevalence of ear symptoms was observed in the dominant ear group, such as tinnitus, 27%, dizziness, 24%, and ear pain, which is often associated with mobile phone use, 18%, while 18% of patients had more than one symptom in one of the ears, and most of them complained of hearing loss in addition to one Other symptoms.Twenty-eight patients (13%) suffered from symptoms of hearing loss, and the remaining cases (14 cases) detected with an audiogram.Conclusion: The radiations produced by cell phones have harmful effects on the ear, and excessive exposure to them may lead to a loss of sensorineural hearing or other symptoms such as tinnitus, dizziness, or ear pain.